Dynamics of Income Inequality among Rice Growers in North West, Nigeria - Albi, Olugbenga Omotayo; Aluwong, Jeremiah Samuel; Agada, Sunday Adole; Kareem, Hamid Kunle; Bayel, Joseph Dauda; Omole, Adebisi Olateju; Yisagana, Comfort Kaka; Atteh, Akinwumi Paul; Ajunwa, Chikezie Gabriel (Nepalese Journal of Agricultural Sciences, 2025)
These studies focused on measurement and dynamics of income inequality among rice growers in North West, Nigeria. A multi-stage sampling design was utilized to select 200 rice growers in North West, Nigeria. Primary data were used based on a well-structured questionnaire. The questionnaire was subjected to validity and reliability test. The data were analyzed utilizing descriptive statistics, Gini-Coefficient, Probit Dichotomous regression model, and Kendall’s coefficient of concordance. The result shows that the mean age of the rice farmers was 43 years, the farmers had 14 years’ experience in rice farming and spent an average of 11 years in attending school education. Furthermore, 80% of the farmers were married, 60% of them were male, 65% had extension contact and 57% belonged to cooperative society. Approximately, 75% of the rice growers belong to high income inequality group, while 25% of the rice growers belongs to low income inequality group. The significant drivers of income inequalities were education and experience at 1% probability level. A t-test results further showed that the t-calculated value of 17.434 which is greater than the t- tabulated value of 1.96 at 5% significance level. This suggests a statistical difference between the average cost (687,251.24) and average returns (1,875,000) of rice production. The substantial positive difference between returns and costs (1,187,748.76) strongly shows that rice production in the study area is economically viable. The challenges encountered by the farmers include lack of land ownership, lack of access to technology, inadequate credit access, poor market information and inconsistent government policy and support.